Prevalence and Risk Factors for Nocturia in an Outpatient Clinic. Issue 3 (9th October 2013) - MIYAZATO, Minoru; TANA, Takeshi; HIGA, Akira; OSHIRO, Takuma; NAMITOME, Ryo; NEZU, Uru; UEDA, Shinichiro; SAITO, Seiichi
<x xml:space="preserve">Abstract</x> Objectives We evaluated the prevalence of and risk factors in patients with nocturia at a general medical clinic in Naha, Japan. Methods We enrolled patients who had been regularly followed‐up at a general medical clinic in Naha. Patients were asked to complete a self‐reported questionnaire regarding medical history and the frequency of nocturnal voids in the last month with anonymity. Univariate and multivariate logistic regression tests were used to evaluate the risk factors for clinically significant nocturia. Results In total, 357 patients (men, 192; women, 165; mean age, 60 years) were eligible for analysis. The prevalence rate of clinically significant nocturia in patients was 33.8%. Univariate, as well as multivariate, analysis revealed that age, gender, and hypertension were significant risk factors for nocturia. Conclusion Clinically significant nocturia is common among patients seen at a general medical clinic. Age and gender are the most definitive risk factors for nocturia. Hypertension may also be related to nocturia. Thus, it is important to evaluate not only urological problems but other medical problems in patients with nocturia.